PENGARUH KEPEMIMPINAN, PEMBERDAYAAN DAN OCB TERHADAP KINERJA MELALUI KEPUASAN KERJA (Studi Kasus Pada Dinas Pertanian dan Kehutanan Kabupaten Rembang) - Agus Sapta Wibawa, 12.5202.0111 (Jurnal Mahasiswa Pasca Sarjana, 2014)
This study aims to examine and analyze that OCB and job satisfaction mediated the effect of leadership and empowerment on the performance of staff at the Department of Agriculture and Forestry Rembang. Sampling was done by census method so that all employees used as a sample except department heads. Engineering test data used in this study include the validity and reliability, multiple regression analysis and significance test to validate the research hypothesis and test mediation. The results showed that; 1) leadership has significant positive effect on job satisfaction, 2) empowering positive has significant effect on job satisfaction, 3) OCB has positive and significant effect on job satisfaction, 4) leadership has significant positive effect on performance, 5) empowerment has positive and significant effect on performance, 6) OCB has positive and significant effect on performance, 7) job satisfaction has significant positive effect on performance, 8) job satisfaction mediated the effect of leadership on performance, 9) job satisfaction mediated the effect of empowerment on performance, 10) job satisfaction mediated the effect OCB on performance. Keywords: leadership, empowerment, OCB (organizational citizenship behavior), job satisfaction, performance